Can pollen affect precipitation? - M. Prank; J. Tonttila; J. Tonttila; X. Shang; S. Romakkaniemi; T. Raatikainen (Atmospheric Chemistry and Physics)
Large primary bioparticles such as pollen can be abundant in the atmosphere; for example near-surface pollen concentrations above 10 000 particles per cubic metre can occur during intense pollination periods. On one hand, due to their large size (10–100 µm), pollen can act as giant cloud condensation nuclei and enhance the collision–coalescence process in clouds that leads to drizzle formation. On the other hand, in humid conditions pollen is known to rupture and release many fine particles that can increase the cloud stability by reducing the droplet size. Additionally, both whole pollen grains and the sub-pollen particles released by pollen rupture are known to act as ice-nucleating particles (INPs). Due to these complex interactions, the role of pollen in modulating the cloud cover and precipitation remains uncertain.